Organização social e regimes de propriedade numa comunidade quilombola paraense - Jose Candido Lopes Ferreira (2013)
Coletivos and individuais are categories that relate to the property regime chosen by a family or community. In the 1990s, during the process of quilombola lands demarcation in Oriximiná, PA, several families have opted to receive individual titles to their lots. The community of Lake Jarauacá, in Acapu River, was divided after the demarcation between families "coletivas" (quillombolas) and "individuais". A new social organization was developed based on the new frontiers that divide the lands in this region. New rules for access and use of resources have become part of life for families of Jarauacá. The work is an exercise in understanding this new social organization and on new formulations about the use and land tenure.